ANALYSIS OF PERSONAL BRANDING AND LEADERSHIP BRANDING COMPANY OWNER AND COMPANY REPUTATION - Fitri Apriyani R Situmorang; Ummi Salamah (Jurnal InterAct, 2018)
Today, many profit or nonprofit organizations, as well as commercial companies, are owned by people who have very strong character in society. With the characteristic of the person's personality, will give the impression to the company as well. Personal branding itself is a planned process in which people make efforts to market themselves. People have to differentiate themselves and stand out from a crowd. Then is to develop an active communication through managing behavior, communication and symbolism. Leadership brand is a reputation for developing exceptional managers with a distinct set of talents that are uniquely geared to fulfill customers 'and investors' expectations. A company with a leadership brand inspires faith that employees and managers will consistently make good on the firm's promises. How is the use of personal and leadership branding, if the person is the owner of a company? What makes the personal and leadership branding matter to the company reputation? Company reputation is the goal as well as an achievement to be achieved for the world Public Relations. For the company, reputation is a form of trust from the society. So, if a company experiences a public trust crisis it will have a negative impact on reputation and will require a lot of effort to grow and rebuild trust, and reputation of course. The reputation that we want to see in this study is from the stakeholders of the company. But how is the relationship between personal branding and leadership branding of company owner on corporate reputation in the eyes of stakeholders?